2015
DOI: 10.1063/1.4922086
|View full text |Cite
|
Sign up to set email alerts
|

Bow-shock instability induced by Helmholtz resonator-like feedback in slipstream

Abstract: Bow-shock instability has been experimentally observed in a low-γ flow. To clarify its mechanism, a parametric study was conducted with three-dimensional numerical simulations for specific heat ratio γ and Mach number M. A critical boundary of the instability was found in the γ-M parametric space. The bow shock tends to be unstable with low γ and high M, and the experimental demonstration was designed based on this result. The experiments were conducted with the ballistic range of the single-stage powder gun m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Finally we note that, although the primary focus in this paper has been on the Vishniac instability, there are a number of other instabilities reported in the literature which depend on the post-shock fluid achieving γ close to 1. In particular there are the bow-shock instabilites described by Dgani et al 11 and Ohnishi et al 24 , which, in light of the results reported in this paper, might be achieved due to ionization or dissociation.…”
Section: Discussionsupporting
confidence: 55%
“…Finally we note that, although the primary focus in this paper has been on the Vishniac instability, there are a number of other instabilities reported in the literature which depend on the post-shock fluid achieving γ close to 1. In particular there are the bow-shock instabilites described by Dgani et al 11 and Ohnishi et al 24 , which, in light of the results reported in this paper, might be achieved due to ionization or dissociation.…”
Section: Discussionsupporting
confidence: 55%
“…Experiments and simulations of Hornung & Lemieux (2001) and Ohnishi et al. (2015) found instability when density jumps of and were reached across the shock. Interestingly, the bifurcation boundary in space is well represented by a constant density ratio of across the shock, plotted with a dashed curve in figure 20.…”
Section: Discussionmentioning
confidence: 98%
“…2009 b ; Ohnishi et al. 2015). Shock instability has been observed by Sirmas & Radulescu (2015, 2019) in molecular dynamic calculations of relaxing shock waves in gases with inelastic collisions, as would occur where strong vibrational relaxation effects are present.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations